Self Efficacy Mahasiswa terhadap Matematika dan Pembelajaran Berbasis Kegiatan Lesson Study - Risnanosanti Risnanosanti (Jurnal Elemen, 2016)
The aim of this research is to description about undergraduate students self efficacy toward mathematics in learning based on lesson study activity. This studied done in mathematics study program of FKIP Muhammadiyah University of Bengkulu in academic year 2015/2016. The subject in this research are undergraduate students whose studied education statistic about 31 students. The instruments are observation sheet and self efficacy scale. The method in this research come from lesson research with lesson study and have three stages namely plan, do and see. This researched have 4 cycles.  Based on data analysis the result of this research is undergraduate student self efficacy is in very good category.